Edukasi Kesehatan Remaja Tentang Pencegahan Stunting di Desa Tibubeneng Kabupaten Badung Propinsi Bali - Kurniasih Widayati; Elfi Kuswati; Ni Luh Made Asri Dewi (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The locus of stunting in 2020 in Bali has increased to five regions, namely Denpasar and Badung districts. One of the stunting loci in Badung district, namely in the Kuta Health Center area, North Kuta sub-district in Tibubeneng Village (BKKBN prop Bali, 2020), obtained data on 342 toddlers, found 32 children with very short status toddlers and 16 children with a total of 48 toddlers (14.04%). From the results of Kurniasih's research (2020), it was found that short mothers (TB <150 cm) are a risk factor for stunting. Stunting is a chronic nutritional problem in toddlers which is characterized by shorter height compared to children of their age. Children who suffer from stunting will be more susceptible to disease and as adults are at risk of contracting degenerative diseases and affecting children’s intelligence level. So this community service activity targets young women as prospective mothers, so they don't give birth to short toddlers (stunting). The activity is carried out by providing education in the form of online counseling activities about health for adolescents. From the results of counseling activities, it was found that the knowledge of adolescents in the Good category increased from 71% to 86%, sufficient knowledge from 24% decreased to 14% and knowledge of less than 5% became 0%